Análise da potencialidade da integração de geração distribuída de energia eólica e solar em Palmas - TO - Araujo, Rogério Rodrigues Lima de (2025)
This study analyzes the feasibility of integrating distributed wind and solar energy generation in Palmas, Tocantins. The research examines the availability of local natural resources, such as solar incidence and wind profiles, and assesses the complementarity between these renewable sources. In-situ measurements and technical and economic feasibility analyses were conducted, considering different application scenarios, including residential and large-scale consumers. The results indicate that despite high solar availability, wind energy's contribution to distributed generation still presents technical and financial challenges. However, integrating these sources can provide advantages in terms of energy security and reducing dependence on non-renewable sources. The study suggests that technological advancements and market condition changes may make this solution more attractive in the future.